2021
DOI: 10.1155/2021/3537968
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence from Sri Lanka for Subphenotypic Diversity within L. donovani-Induced Classical Cutaneous Leishmaniasis

Abstract: Sri Lanka reports a large focus of Leishmania donovani-induced cutaneous leishmaniasis (CL) with CL as the main clinical entity. Two independent, long existed, and clinicoepidemiologically different transmission foci in the northern region (NR) and southern region (SR) were recently reported. Current project is an extension to this previous study. Clinical diversity within a profile of classical cutaneous leishmaniasis (CCL) in a focus of L. donovani-induced CL is described for the first time. Patients with la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…ITS1 is a highly conserved region; however, the associated polymorphisms allow differentiation between species [ 29 ]. The genetic heterogeneity of L. donovani in Sri Lanka is evident through many factors (listed), which can contribute to the differing sensitivity between diagnostic techniques: (i) genomic analysis of L. donovani isolates of global distribution showed that the isolates fell into five large groups based on geographic origin but showed vast genetic variation within these groups (this study included Sri Lankan isolates) [ 30 ]; (ii) sub-phenotypic variation in classical CL caused by L. donovani was evident between the northern and southern foci of disease transmission in Sri Lanka, suggesting strain differences [ 31 ]; (iii) high haplotype diversity, with sub-clusters showing clinically relevant characteristics [ 32 ]; (iv) emergence of treatment failure and non-responsiveness to standard treatment [ 17 , 33 ], which is multifactorial in origin, but genetic variations contribute [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…ITS1 is a highly conserved region; however, the associated polymorphisms allow differentiation between species [ 29 ]. The genetic heterogeneity of L. donovani in Sri Lanka is evident through many factors (listed), which can contribute to the differing sensitivity between diagnostic techniques: (i) genomic analysis of L. donovani isolates of global distribution showed that the isolates fell into five large groups based on geographic origin but showed vast genetic variation within these groups (this study included Sri Lankan isolates) [ 30 ]; (ii) sub-phenotypic variation in classical CL caused by L. donovani was evident between the northern and southern foci of disease transmission in Sri Lanka, suggesting strain differences [ 31 ]; (iii) high haplotype diversity, with sub-clusters showing clinically relevant characteristics [ 32 ]; (iv) emergence of treatment failure and non-responsiveness to standard treatment [ 17 , 33 ], which is multifactorial in origin, but genetic variations contribute [ 34 ].…”
Section: Discussionmentioning
confidence: 99%